The Effect of Students’ Learning Style on Their Writing Achievement - Ahmad Aziz Hanafi (Graduate Program, University of Islam Malang, 2019)
AbstractThe purpose of this study is to know whether there is a significant difference in students writing Achievement among students with visual, audio, and kinesthetic learning styles. The study was carried out in a population of 120 students of grade XI at MAN 3 Bahrul Ulum Jombang. The researcher was used incidental sampling, incidental sampling is used to classify students' preference in learning particular differentiate from students’ learning style learners and as many as 90 students as sample. The questionnaire was prepared to collect the data concerning with the students' major learning preference and the test which designed in the form of writing an essay was used to measure students' writing skill. To achieve the aim of the study, the data were analyzed by using analysis of variance (ANOVA) with help of SPSS 20.0. The researcher found that result of hypothesis testing F-testValue was (0.578) and the significant value is (0.563). Because the significant value is greater than 0.05 the mean was declared not significantly different. It means that students learning style on their writing achievement did not differ between the visual learners, the auditory learners, and the kinesthetic learners. Based on the result of this study, the researcher discovered that there is no significant difference in writing achievement among students with visual, auditory, and kinesthetic learning styles. Keywords: comparison, effect, learning styles, writing achievement